Pupillary Response to Negative Emotional Stimuli Is Differentially Affected in Meditation Practitioners - Vasquez-Rosati, Alejandra; Brunetti, Enzo P.; Cordero, Carmen; Maldonado, Pedro E. (Frontiers in Human Neuroscience, 2017)
Clinically, meditative practices have become increasingly relevant, decreasing anxiety in patients and increasing antibody production. However, few studies have examined the physiological correlates, or effects of the incorporation of meditative practices. Because pupillary reactivity is a marker for autonomic changes and emotional processing, we hypothesized that the pupillary responses of mindfulness meditation practitioners (MP) and subjects without such practices (NM differ, reflecting different emotional processing. In a group of 11 MP and 9 NM, we recorded the pupil diameter using video-oculography while subjects explored images with emotional contents. Although both groups showed a similar pupillary response for positive and neutral images, negative images evoked a greater pupillary contraction and a weaker dilation in the MP group. Also, this group had faster physiological recovery to baseline levels. These results suggest that mindfulness meditation practices modulate the response of the autonomic nervous system, reflected in the pupillary response to negative images and faster physiological recovery to baseline levels, suggesting that pupillometry could be used to assess the potential health benefits of these practices in patients.